Peran Tokoh Agama dalam Pembinaan Harmonisasi Kehidupan dan Akhlak Masyarakat di Kota Metro Lampung - Ida Umami (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Religious figures basically have a very important and strategic position and role, mainly as a spiritual, moral and ethical foundation in the life and life of mankind. a religious figure is a figure or role model in society. Has a position and great influence in the midst of society, because it has advantages, both in science, integrity, and so forth. Religious figures also serve as community leaders, as priests in religious matters and community issues and state affairs in order to succeed government programs and foster community life harmonization. Religion as a value system must be understood, lived and practiced by all adherents in the life order of every individual, family and society and animates the life of the nation and the state. The current situation of harmonization and community behavior requires the role of religious leaders to be significantly expected to take the initiative in the development and development of morality. This means that every development effort must always be directed to have a positive impact on character development. Keyword: Religious figures and character development